Preoperative Predictive Factors of Conversions in Laparoscopic Splenectomies. Issue 3 (June 2018) - Vecchio, Rosario; Milluzzo, Sebastian M.; Troina, Graziano; Cacciola, Emma; Cacciola, Rossella R.; Catalano, Renato S.; Caputo, Marco
Abstract : Purpose: Presently, laparoscopic splenectomy (LS) is being performed for several indications in clinical practice. However, conversion to open surgery is occasionally required in some patients. We analyzed the intraoperative indications and potential preoperative predictors associated with conversion to open surgery in those presenting for LS. Methods: We reviewed 107 patients who underwent LS. We analyzed the surgical indications, spleen size, surgical procedure performed, operative time, rate of and indications for conversions, as well as postoperative complications. Results: Among the 15 patients (14.0%) who underwent conversion, the conversion was related to the occurrence of a splenic lymphoma in 10, severe bleeding in 3, a lack of anatomic definition in 1, and splenic candidiasis in 1 patient. A comparison between the results obtained in the initial 30 patients (LS performed during the learning curve) and those obtained in the remaining 77 patients, showed that conversions appeared to be related to the experience/expertise of the surgical team excluding patients with splenic malignancies. Conversion was not associated with a higher morbidity-mortality rate, but only a longer length of hospitalization. Conclusions: LS is a gold standard procedure when performed by experienced and competent surgeons. However, careful patient selection is recommended before using the laparoscopic approach in those presenting with splenic malignancies.